2015
DOI: 10.3174/ajnr.a4510
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of T1 Relaxation, ADC, and Fractional Anisotropy during Early Brain Maturation: A Serial Imaging Study on Preterm Infants

Abstract: BACKGROUND AND PURPOSE:The alteration of brain maturation in preterm infants contributes to neurodevelopmental disabilities during childhood. Serial imaging allows understanding of the mechanisms leading to dysmaturation in the preterm brain. The purpose of the present study was to provide reference quantitative MR imaging measures across time in preterm infants, by using ADC, fractional anisotropy, and T1 maps obtained by using the magnetization-prepared dual rapid acquisition of gradient echo technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 37 publications
(48 reference statements)
5
52
3
1
Order By: Relevance
“…For example, over the years several studies have shown that even intra-cortical myelin can be probed through the T1-shortening caused by myelin, giving rise to MR signal differences along the cortical rim [127129]. In white matter fibres, T1 undergoes profound changes in development [130]. Recently, it was shown in adults that variations in T1 can be explained in terms of a combination of other quantitative MR parameters, regardless whether grey or white matter areas are considered [14].…”
Section: Discussionmentioning
confidence: 99%
“…For example, over the years several studies have shown that even intra-cortical myelin can be probed through the T1-shortening caused by myelin, giving rise to MR signal differences along the cortical rim [127129]. In white matter fibres, T1 undergoes profound changes in development [130]. Recently, it was shown in adults that variations in T1 can be explained in terms of a combination of other quantitative MR parameters, regardless whether grey or white matter areas are considered [14].…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal scans from 9 very prematurely born infants (4 males, mean gestational age: 27.3 weeks ± 1.0 day) acquired at term equivalent age (TEA, mean age at scan 41.0 weeks ± 2.0 days) were selected from a prospective cohort of neonates born before 30 weeks of gestation conducted between February 2011 and May 2013 in the level III neonatology unit at the University Hospital of Lausanne, Switzerland [40]. This cohort included solely children considered as ‘cerebral low-risk’, meaning that they showed no evidence for severe intraventricular haemorrhage grade III-IV and/or parenchymal haemorrhagic infarction, no high grade periventricular leucomalacia, no congenital malformations or genetic abnormalities and had normal neurological assessment at TEA according to the Hammersmith Neonatal Neurologic Examination from [41].…”
Section: Methodsmentioning
confidence: 99%
“…Recently developed MRI sequences sensitive to microstructural changes in the cerebral cortex and the WM (diffusion tensor, T1-mapping) have emerged as sensitive assays to study developmental related changes in human brain [3640]. Our study is designed in two parts.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that even in the absence of structural brain injury, the developmental trajectory of the preterm brain is altered over the third trimester. Evidence of clinical 4 .01 * 14.17 ± 1.6 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] 13.91 ± 2.7 [8][9][10][11][12][13][14][15][16][17][18][19][20] .66…”
Section: Discussionmentioning
confidence: 99%